2022
DOI: 10.1039/d2nj02266d
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically porous single catalyst Ru/HPW/UiO-66 with synergistic acid/metal sites for one-pot catalytic synthesis of γ-valerolactone

Abstract: γ-valerolactone (GVL) is an important lignocellulosic platform molecule with huge potential for various industrial and chemical applications, which is usually produced by using Levulinic acid (LA) or its esters as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The peaks with binding energies at 37.8 eV and 35.8 eV are attributed to W 4f 5/2 and W 4f 7/2 of W 6+ in TPA [31]. Surprisingly, an additional weak energy peak appeared at 29-33 eV, which was probably due to the partial decomposition of TPA leading to the formation of a lower chemical valence [32]. This demonstrated that the introduced TPA groups have been loading on the framework, in agreement with XRD and FTIR results.…”
Section: Catalyst Characterizationmentioning
confidence: 93%
“…The peaks with binding energies at 37.8 eV and 35.8 eV are attributed to W 4f 5/2 and W 4f 7/2 of W 6+ in TPA [31]. Surprisingly, an additional weak energy peak appeared at 29-33 eV, which was probably due to the partial decomposition of TPA leading to the formation of a lower chemical valence [32]. This demonstrated that the introduced TPA groups have been loading on the framework, in agreement with XRD and FTIR results.…”
Section: Catalyst Characterizationmentioning
confidence: 93%